Clinical and manometric profile of patients with GERD in a tertiary care hospital - Deepalakshmi, Kaliyaperumal; Vasanthi, Ramesh; Venkatakrishnan, Leelakrishnan; Karthikeyan, Shanmugam (International Journal of Advances in Medicine, 2017)
Background: Abnormal esophageal motility and low Lower Esophageal Pressure (LES) play an integral role among various etiologies implicated in pathogenesis and severity of Gastro Esophageal Reflux Disease (GERD). Delayed clearance of refluxate leads to prolonged mucosal exposure to gastro duodenal contents which promotes esophagitis and its complications. To find out the association of ineffective esophageal motility (IEM) and low Lower Esophageal Sphincter (LES) pressure with endoscopic esophagitis in patients presenting with symptoms of GERD. Settings and designs: Prospective cross sectional study done in a tertiary medical care center in south India from October 2016 to March 2017. Methods: This cross sectional study was carried out among patients presenting with symptoms of GERD (heart burn and regurgitation,) at least twice per week for past three months. Based on their endoscopy findings patients with GERD are grouped into two having erosive and nonerosive reflux disease. After general and systemic clinical examination, High resolution Manometry was performed, and data was analyzed using Trace 1.2.3a V software. Statistical methods: Data was analysed using SPSS version 19. Chi square test was used to analyze categorical variables and independent ’t’ test was used for continuous variables. Results: A total of 66 patients with GERD symptoms were subjected to esophageal manometry. Out of these 66 patients 42 were males and 22 were females with their mean age 40.82±12.86 years. Among 66 patients presented with GERD symptoms 26.7% were found to have ineffective esophageal motility and only 11.7% had low LES pressure. Ineffective esophageal motility was also found to be more common among older age group individuals with their mean age being 44.64 ±14.154. Among the patients with erosive reflux disease (70.21%), 66.7% had low LES pressure and 75 % had IEM; the association was not statistically significant. Conclusions: The incidence of Ineffective esophageal motility in patients with GERD is found to be higher than that of low LES pressure. There was no significant association observed between IEM and low LES pressure with endoscopic esophagitis in patients with GERD.